Homeplug AV and IEEE 1901 : a handbook for PLC designers and users - Latchman, Haniph A. (Hoboken, New Jersey : IEEE Press/Wiley., 2012)
The only authorized book explaining the HomePlug networking standards HomePlug is a growing technology for creating highspeed Power Line Communication (PLC) networks by transmitting data over inhome or inoffice power lines. Users only need to plug adapters into wall outlets to create an instant network of computers, printers, routers, home entertainment devices, and appliance control systems. HomePlug AV and IEEE 1901: A Handbook for PLC Designers and Users provides for the first time an opportunity for nonmembers of the HomePlug Alliance to gain indepth insight into the design and operation of the HomePlug standards. Offering a clear and simple description of the standards, this groundbreaking resource presents HomePlug AV and the associated IEEE 1901 standards in terms more readily understood by a much wider audience, including nontechnical managers, engineers, students, and HomePlug designers. The book details the many benefits of HomePlug AV, including: An affordable, secure alternative or complement to WiFiespecially in buildings where WiFi reception is poor or running new network wires is impractical Higher potential data transmission rates up to 200 Mbps Support for multimedia applications such as HDTV and VoIP The book also provides an overview of the HomePlug Green PHY standard that is targeted for use in smart energy applications, and the HomePlug AV 2.0 standard that operates at up to 1.5 Gbps. An essential tool for designers of HomePlug devices, network administrators, and individual users of HomePlug networks who need to understand the features and capabilities of HomePlug, HomePlug AV and IEEE 1901: A Handbook for PLC Designers and Users will also prove useful for researchers in academia and the power line communications industry.
Includes bibliographical references (pages 334-335) and index.
Print version record and CIP data provided by publisher.
Keywords: Electric lines -- Carrier transmission -- Design and construction; Home computer networks -- Design and construction; COMPUTERS -- Data Transmission Systems -- General; Electronic books